The Historical Value of Dickens’s A Tale of Two Cities (Journal of the College of Education for Women, 2019)
In "historical" fiction, characters that never really existed, give expression to the impact of historical events on the people who really did live through them. The result is not history, as an accurate record of actual events, but fiction in which an earlier age is rendered through the personal joys and sufferings of characters. This paperaims at investigating the historical realities presented in Dickens’s A Tale of Two Cities.